KONFLIK BATIN TOKOH DALAM NOVEL “SANG PEMIMPI” KARYA ANDREA HIRATA (Teori Sigmund Freud) - Fatbiagunna; Hamsa, Akmal; Hajrah (Journal of Applied Linguistics and Literature, 2025)
This study aims to describe the internal conflicts of the main character, the internal conflicts of the supporting characters, and the differences between the internal conflicts of the main character and the supporting characters in Andrea Hirata's novel ‘Sang Pemimpi’ (The Dreamer). This study uses a qualitative descriptive method, with data sources found in the novel ‘Sang Pemimpi’ by Andrea Hirata. The data in this study are in the form of sentences found in the novel ‘Sang Pemimpi’. The research instrument used is the researcher himself, assisted by data cards. The data collection techniques used in this study are reading and recording techniques. The data analysis techniques used in this study were classification, description, and conclusion. The results of the study show that (1) the form of internal conflict experienced by the main character in the novel ‘Sang Pemimpi’ by Andrea Hirata is sadness, hope, anxiety, worry, anger, and a sense of loss, so the internal conflict experienced by the main character is more dominant in the form of avoidance-avoidance. (2) The forms of inner conflict experienced by the supporting characters in Andrea Hirata's novel ‘Sang Pemimpi’ are hope, anger, disappointment, and fear. Therefore, the inner conflict experienced by the supporting characters is more dominant in the avoidance-approach conflict. As for (3) the difference in the form of inner conflict between the main character and the supporting characters, the main character is more dominated by avoidance-avoidance conflict, while the supporting characters are more dominated by avoidance-approach conflict.